Pemanfaatan Model Blended Learning untuk Meningkatkan Motivasi dan Hasil Belajar IPA Materi Tekanan Peserta Didik Kelas VIII E SMP Negeri 2 Bojongsari Tahun Pelajaran 2015/2016 - Riyanto, Nokman (Jurnal Profesi Keguruan, 2016)
The outline of the research issue in this class activity research is how the use of blended learning model to increase motivation and results of science material pressure on science’ study of student on class VIII E 2 Bojongsari Junior High School in scool year 2015/2016. The steps of research include planning, action, observation, and reflection. Data collection research using questionnaires, observation, and interviews. Data validation using rational data analysis based on the results of the response and resulths of Deuteronomy students. This research uses descriptive analytic as data. Based on the results, the data of the student`s motivation increase 15.43% whereas the results of the study show improvement 22.92%. The conclution of the study explaine that the application of blended learning models can enhance understanding, motivation of students and the learning outcomes student on class VIII E 2 Bojongsari Junior High School.